Cancers Primitifs Oto-Rhino-Laryngologiques Et Cervico-Maxillo-Faciaux De L’enfant: Aspects Épidémiologiques Et Histopathologiques - W., Foma; B., Amana; E., Pegbessou; H., Bissa; S., Adam; W., Dolou; T., Darré; E., Kpemissi (European Scientific Journal, ESJ, 2016)
Objective: Have a view on child’s head and neck cancers in a reference centre in Togo. Methodology: It was a descriptive retrospective study about the cancers diagnosed among children under 15 years in head and neck department of Sylvanus Olympio Teaching Hospital of Lomé in Togo from 1st January 2005 to 31 December 2014. The pieces were analysed in the pathological anatomy laboratory of the same teaching Hospital. Results: The child’s head and neck cancers represented 0.8 % of the whole ENT tumours and 5.5% of head and neck cancers. The average age was 8 years ± 4.7 ranging from 3 months to 15 years. The male sexe was predominant in 15 cases. The frequent location was ganglions, followed by oral cavity (gingivo-maxillary location and gingivo-mandibular location) in respectively 13 and 6 cases. The sinus, rhinopharynx, and larynx locations were found in 01 case of each cancer. In terms of histopathology, there were 21 cases of non-Hodgkin’s lymphoma of which 09 cases of Burkitt’s and 01 case of inferior lip neuroblastoma. Conclusion: Child’s head and neck cancers are scarce in Togo and dominated by malignant primitive cervical adenopathy.